Relevansi Pendidikan Akhlak Islam terhadap Krisis Moral Generasi Digital dalam Perspektif Syekh Az Zarnuji - NURUL HAYATI; Sumiyati; Amaliatul Fitriyah; Safitrianingsih; Ahsan Hakim (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study examines the relevance of Islamic moral education in addressing the moral crisis of the digital generation through the perspective of Shaykh Az-Zarnuji. In the digital era, characterized by the decline of ethics due to unlimited exposure to technology, the teachings in Ta‘lim al-Muta‘allim offer essential moral and pedagogical guidance. The purpose of this research is to analyze Az-Zarnuji’s thoughts on moral education—including his perspectives, sources, approaches, and technical proceduresand to reinterpret his teachings  within the context of modern moral challenges. The research employs a library research method using a content analysis approach applied to Az-Zarnuji’s primary works and contemporary literature on digital ethics. The findings reveal that Az-Zarnuji’s concept of moral education centers on sincerity of intention, discipline in seeking knowledge, and respect for teachers. These values provide a meaningful solution to the moral crisis of the digital era, which is characterized by narcissism, moral relativism, and the loss of social empathy. Theoretically, this study enriches Islamic education discourse by linking classical thought with contemporary moral issues. Practically, the findings serve as a reference for educators and policymakers in integrating Islamic spiritual and ethical values into digital education curricula. Thus, Az-Zarnuji’s teachings remain profoundly relevant in fostering moral awareness among the digital generation in the modern era.